2019
DOI: 10.1029/2018jd029766
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Study of North Atlantic Summer Cyclone Activity in Dynamical Downscaled Simulations

Abstract: We conduct a sensitivity study of the North Atlantic cyclone climate, with respect to the cumulus parameterization (CP) and planetary boundary layer (PBL) schemes, applied in the dynamical downscaling of HadGEM2‐ES simulations using Polar Weather Research and Forecasting. A set of seven sensitivity experiments is conducted for 1979–2004 using these CP and PBL schemes. CP schemes are Kain‐Fritsch (KF), Zhang‐McFarlane (ZM), and the modified Tiedtke (TZ). PBL schemes are the local Mellor‐Yamada‐Janjić (MYJ), Mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As also stated in the study undertaken by Munsi et al (2021), notwithstanding that the WRF model simulation can reproduce the maximum stages of the cyclone systematically, the initial track should be carefully handled so that the deviation can be minimised. Not only are they the consequences of the forcing data, but the deviations might also stem from the sensitivity parameters of the model itself (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As also stated in the study undertaken by Munsi et al (2021), notwithstanding that the WRF model simulation can reproduce the maximum stages of the cyclone systematically, the initial track should be carefully handled so that the deviation can be minimised. Not only are they the consequences of the forcing data, but the deviations might also stem from the sensitivity parameters of the model itself (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our pragmatic assumption is that the processes resolved by different climate models, explicitly including sub-synoptic and R. E. Danielson et al: Possible impacts of climate change on fog in the Arctic and subpolar North Atlantic larger scales, provide a basis for estimating the future trend in fog occurrence. Contemporary studies, both observed and modelled (Dorman et al, 2017;Zhang and Lewis, 2017;Tardif, 2017;, highlight that fog formation and dissipation are indeed sensitive to these resolved scales. In an attempt to approach the fog-process scales, we apply a regional model downscaling of Hadley Center Earth System model (HadGEM2) global climate simulations (Zhang et al, 2019a, b) to provide an enhanced representation of radiative processes and moist energy transports.…”
Section: Introductionmentioning
confidence: 99%